ALP search using precessing light in a magnetized Fabry Perot cavity. Issue 4 (1st April 2022) - Creswick, R.J.; Avignone, F.T.
Abstract: In this paper we outline an experiment to detect the conversion of photons to axion-like particles (ALPs) in a strong magnetic field. We show that by modulating the polarization of the light passing through a Fabry-Perot cavity so that it effectively precesses at the modulation frequency, a signal is produced that is proportional to the square, as opposed to the fourth power, of the ALP-photon coupling constant. Assuming shot noise to be the dominant source of noise, we estimate that this approach is sensitive to ALP masses less than 10 -4 eV and couplings on the order to gaγ > 1.6 × 10 -11 GeV -1 with a 10 m, 10 T magnet, and gaγ > 1.6 × 10 -12 GeV -1 with a 100 m magnet as envisaged by ALPs-IIc. ALPs with these properties have been invoked to explain the apparent transparency of the extragalactic background light (EBL) to ultra high-energy gamma rays emitted by BLAZARs.